Impact of protein malnutrition on exogenous reinfection with Mycobacterium tuberculosis. - McMurray, D. N. (1989)
Malnutrition may be a predisposing host factor in the development of exogenous-reinfection tuberculosis. Outbred Hartley guinea pigs were given isocaloric diets containing either 30% ovalbumin (control animals) or 10% ovalbumin (low-protein-fed [LP] animals). Equal numbers of control and LP animals were assigned to one of three infection groups: (i) primary pulmonary infection with a low-virulence, streptomycin-resistant (LVsr) isolate of Mycobacterium tuberculosis and then reinfection 6 weeks later by the same route with a high-virulence (HV) isolate; (ii) only the primary infection (LVsr isolate); and (iii) only the secondary infection (HV isolate). Each infection resulted in the development of 4 to 12 pulmonary tubercles. Guinea pigs were skin tested with purified protein derivative and killed 6 weeks after the second infection. Protein deprivation suppressed the dermal responses to purified protein derivative in all infection groups. Primary infection of well-nourished animals with the LVsr isolate induced significant protection against infection with the HV isolate in the reinfected group, based upon the numbers of viable mycobacteria in the lung and spleen. Protein malnutrition did not exacerbate disease in the reinfected group beyond that observed in malnourished animals infected with the HV isolate only, but neither did the infection with the LVsr isolate protect the LP animals against reinfection with the HV isolate. We conclude that malnutrition interferes with the protection normally afforded by primary infection but does not result in more severe disease in reinfected individuals than would be observed in singly infected subjects.